2022
DOI: 10.1177/20417314221111868
|View full text |Cite
|
Sign up to set email alerts
|

Peptide nanogels as a scaffold for fabricating dermal grafts and 3D vascularized skin models

Abstract: Millions of people worldwide suffer from skin injuries, which create significant problems in their lives and are costly to cure. Tissue engineering is a promising approach that aims to fabricate functional organs using biocompatible scaffolds. We designed ultrashort tetrameric peptides with promising properties required for skin tissue engineering. Our work aimed to test the efficacy of these scaffolds for the fabrication of dermal grafts and 3D vascularized skin tissue models. We found that the direct contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
(116 reference statements)
1
5
0
Order By: Relevance
“…Here we demonstrate that peptide based nanogels, containing the Fmoc-FF building block as an internal core and a couple of surfactants (TWEEN ® 60/SPAN ® 60), enter MDA-MB-231 cells mostly via caveolae-mediated endocytosis. This result could be expected for our NGs, taking into account some studies that predicted the mechanism of entry into the cells as a function of the nanoparticle features [ 35 , 40 , 44 ]. These studies point out that caveolae-mediated endocytosis is favored for small nanoparticles with a size lower than 200 nm, an external surface coated by polyethylene glycol (PEG), and a negative net charge.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Here we demonstrate that peptide based nanogels, containing the Fmoc-FF building block as an internal core and a couple of surfactants (TWEEN ® 60/SPAN ® 60), enter MDA-MB-231 cells mostly via caveolae-mediated endocytosis. This result could be expected for our NGs, taking into account some studies that predicted the mechanism of entry into the cells as a function of the nanoparticle features [ 35 , 40 , 44 ]. These studies point out that caveolae-mediated endocytosis is favored for small nanoparticles with a size lower than 200 nm, an external surface coated by polyethylene glycol (PEG), and a negative net charge.…”
Section: Discussionsupporting
confidence: 72%
“…Even though different classes of polymer-based nanogels have been reported, only rare examples of nanogels originated by using peptide building blocks have been listed in the literature until now [ 38 , 39 , 40 ]. Recently, we studied and mutually analyzed three different methodologies for the Fmoc-FF nanogel formulation, namely water/oil emulsion (W/O), top-down strategy, and nanogelling in water.…”
Section: Discussionmentioning
confidence: 99%
“…In order to solve this issue, embedding cells in biomaterial-based scaffolds to confine injected cells at the location of transplantation without run-off has been deeply assessed 15 17 . IVFK hydrogels provide cell attachment sites for mouse myoblasts, significantly prolonging cell survival and supporting their expansion and differentiation into myotube myocytes 28 . It was reported that the combination of engineered fibrin hydrogel and MSCs could localize more cells at the wound site, which revealed better wound repair effects than the transplantation of MSCs alone 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Cells typically adhere rather poorly to these synthetic polymers, therefore they are usually employed in combination with natural polymers, which seem to be crucial for the physiological character of a reliable in vitro skin model [ 79 ]. Peptide-based hydrogels are another promising approach for tissue engineering HSEs [ 83 , 84 ]. Moreover, a method of a “self-assembled skin equivalent” has been described, providing an approach without any artificial scaffold components [ 67 ] ( Figure 3 C).…”
Section: Human Skin Equivalentsmentioning
confidence: 99%